Nilai-Nilai Keislaman pada Pendidikan Ketarunaan (Studi terhadap SMK Pelayaran Buana Bahari Cirebon) - Mukhlisin, Mukhlisin; Sofy, Malik; Hadi, Dede Sofyan; Uspitawati, Uspitawati (Universitas Islam Sultan Agung, 2023)
The purpose of conducting research on Islamic values in cadet education is to explore, identify and analyze the application of the process of cadet education programs, Islamic values in cadet education, as well as the advantages and disadvantages of cadet education at Vocational High School Pelayaran Buana Bahari Cirebon. The research method used is a qualitative approach. The data collection technique is first, using interviews with principals, teachers, instructors, cadets and parents. Second, observation on educational activities for 24 hours. Third, the study of documentation on archives and documents at SMK Pelayaran Buana Bahari Cirebon. The results show that the youth education system is by implementing a boarding or boarding program with a semi-pesantren approach, class learning according to scheduled subjects, ceremonies and apples every morning and evening, sports by running and push-ups, congregational prayers, congregational yasinan, commemoration of Islamic Holidays and mental and character development of cadets. The Islamic values obtained by the cadets are religious values, commendable moral values to teachers, the value of caring for social and environmental concerns, the value of religious moderation and the value of love for the homeland. The advantages of cadet education are the balance of spiritual, intellectual and physical aspects of cadets. Meanwhile, the weakness of cadet education is the existence of a punishment syndrome, the presence of thick seniority, negative parents' suspicions on the school and the tight schedule of cadet activities that drain the cadets' energy and minds.